COMPARISON ANALYSIS OF RISK-BASED CAPITAL (RBC) PERFORMANCE AND ITS EFFECT ON ISLAMIC INSURANCE PROFITABILITY IN INDONESIA AND MALAYSIA - Zubaidah Nasution; Elfira Maya Adiba; Mohamed Omar Abdulrahim (al-Uqud : Journal of Islamic Economics, 2019)
The minimum value of risk-based capital of Islamic insurance is 30% in Indonesia, while Malaysia is 130%. RBC is one of indicator to measure people interest in Islamic insurance products. This paper aims to compare the risk-based capital (RBC) of Islamic insurance companies in Indonesia and Malaysia and analyze its financial ratios. This study used quantitative approach through two analysis techniques, the Mann-Whitney test and multiple linear regression. The results of this study showed that there is difference in risk between capital (RBC) of Indonesian and Malaysian Islamic insurance. Further, RBC, liquidity and investment balance ratios have a significant impact to the profitability of Islamic Insurance in Indonesia, while investment returns have no significant impact. In the other hand, RBC, liquidity, investment balance ratio, and investment returns have significant impact to the profitability of Islamic Insurace in Malaysia.